PRAKTEK PERKAWINAN DI BAWAH UMUR MENURUT HUKUM ISLAM DAN HUKUM PERKAWINAN DI INDONESIA - Murni Yanti; Imran Imran; Hendra Surya (AL-ILMU, 2021)
According to Islamic law, what is meant by marriage is a contract that justifies association and limits rights and obligations as well as mutual assistance between a man and a woman who are not between the two of them.